Improving police officers’ perceptions of sexual offending through intensive training - Darwinkel, Elli (Criminal justice and behavior, 2013)
We examined whether specialist police training on the dynamics of sexual offending can modify officers' victim-blaming attitudes and negative perceptions regarding likely case authorization. The sample included 77 Australian police officers specialising in sexual assault investigation. The training, delivered face to face over 4 weeks, included focus on identifying elements of grooming in offending relationships and how these elements can be elicited from victims and suspects within a narrative interviewing framework. Officers' perceptions of cases were assessed immediately pre- and posttraining using a series of case scenarios. For each scenario, officers rated (on a 10-point Likert-type scale) their confidence that the case should be authorised to proceed to prosecution and the responsibility attributable to the victim. For each case, officers also listed up to 5 factors to justify their case authorization decision. Overall, confidence in case authorization increased from pre- to posttraining, whilst perception of victim "responsibility" decreased. The pattern of results, including the qualitative evidence to justify officers' decisions, support that the attitude change was due to greater understanding of the dynamics of sexual offending. The implications for police trainers, and directions for future research, are discussed.